Nonclinical safety assessment of a human interleukin‐22FC IG fusion protein demonstrates in vitro to in vivo and cross‐species translatability. Issue 6 (15th November 2018) - Lee, Donna W.; Zhong, Shelly; Pai, Rama; Rae, Julie; Sukumaran, Siddharth; Stefanich, Eric G.; Lutman, Jeff; Doudement, Estelle; Wang, Xiaoting; Harder, Brandon; Lekkerkerker, Annemarie; Herman, Ann; et al.
Abstract: Although Interleukin‐22 (IL‐22) is produced by various leukocytes, it preferentially targets cells with epithelial origins. IL‐22 exerts essential roles in modulating various tissue epithelial functions, such as innate host defense against extracellular pathogens, barrier integrity, regeneration, and wound healing. Therefore, IL‐22 is thought to have therapeutic potential in treating diseases associated with infection, tissue injury or chronic tissue damage. A number of in vitro and in vivo nonclinical studies were conducted to characterize the pharmacological activity and safety parameters of UTTR1147A, an IL‐22 recombinant fusion protein that links the human cytokine IL‐22 with the Fc portion of a human immunoglobulin. To assess the pharmacological activity of UTTR1147A, STAT3 activation was evaluated in primary hepatocytes isolated from human, cynomolgus monkey, minipig, rat, and mouse after incubation with UTTR1147A. UTTR1147A activated STAT3 in all species evaluated, demonstrating that all were appropriate nonclinical species for toxicology studies. The nonclinical safety profile of UTTR1147A was evaluated in rats, minipigs, and cynomolgus monkeys to establish a safe clinical starting dose for humans in Phase I trials and to support clinical intravenous, subcutaneous and/or topical administration treatment regimen. Results demonstrate the cross‐species translatability of the biological response in activating the IL‐22 pathway as well as the translatability of findings from in vitro to in vivo systems. UTTR1147A was well tolerated in all species tested and induced the expected pharmacologic effects of epidermal hyperplasia and a transient increase in on‐target acute phase proteins. These effects were all considered to be clinically predictable, manageable, monitorable, and reversible.